Analisis Kelayakan Elektrikal Material Resin Epoksi Silane Sebagai Material Isolator Tumpu Dengan Desain Dua Sirip Terpisah - Prasetya, Widagdo; Mahdi Manggala, Andhip (ELECTRON Jurnal Ilmiah Teknik Elektro, 2022)
An insulator is one of the electric power equipment functioning as insulation that limits the voltage area from the non-voltage area. The insulators of the medium voltage air line network in terms of their function are classified into suspension insulators and line insulators. The line insulators function as a support for the voltage network on a straight line. In this study, a line insulator was made of several fillers, namely epoxy resin as the main material and silica and silaene sand as supporting materials. The parameters for testing the insulator including breakdown voltage, insulation resistance and tangent delta measurement. Testing is carried out at PT. PLN (Persero) UPDL Semarang. The results of the breakdown voltage on the epoxy resin propulsion insulator with two conditions, wet and dry conditions, it was found 100 kV in dry condition and 70 kV in wet condition and still in accordance with PLN standars, namely at least 65 kV in wet conditions. The measurement of  insulation resistance in dry conditions, it was found more than 1000 G Ω. Referring to the international standard reference VDE ( catalouge 228/4) with  insulation resistance of 1 M Ω  per 1 kV, the results are in accordance with the standard. Then the measured of tangent delta, the largest value obtained 0.495% at the largest input voltage is 9.99 kV. The tangent delta measurement fall into the "GOOD" category when referring to the ANSI C 57.12.90 standard, where the tangent delta less than 0.5% is included in the "GOOD" category.